The impact of benefit cognition on residents' willingness to participate in low-carbon community construction: an empirical study based on cognitive behavioral theory - Chunling Sun; Zheyuan Zhang; Tingjun Li; Huijie Jiang (Frontiers in Sustainable Cities, 2025)
Residents are the core driving force in community construction, and enhancing their willingness to participate is crucial for advancing low-carbon community development. Based on cognitive behavioral theory, this study explores the impact of benefit cognition on residents' willingness to participate in low-carbon community construction. An E-prime experiment was designed with a 2 (Benefit Cognition: high/low) × 2 (Government Subsidy: yes/no) × 2 (Household Income: high/low) framework, selecting five common low-carbon community construction projects as the context, to examine the moderating effects of government subsidies and household income. The results indicate that residents' benefit cognition has a significant positive effect on their willingness to participate in low-carbon community initiatives. Both government subsidies and household income positively moderate the relationship between benefit cognition and residents' willingness to participate; however, the interaction between government subsidies and household income does not significantly moderate the effect of benefit cognition on residents' willingness to participate. This study provides empirical support for policymakers, community managers, and relevant stakeholders, offering practical guidance, particularly in enhancing benefit cognition awareness and designing subsidy policies, to promote residents' involvement in low-carbon community construction.